IDEOLOGY BEHIND POLITENESS - Sosiowati, IGAG; Budiarsa, Made; Simpen, I Wayan (e-Journal of Linguistics; Vol. 8. Januari 2014 No. 1)
Politicians are considered to be the ones whose honesty is doubtful. This is proven by the fact that there are a lot of negative perception about them. Most of the people know that their ideology is power. In public discussion they often violate or apply politeness with the purpose to get as much power as possible. How polite they are in using the language will be measured by the combination of Grice’s maxims of cooperative principles (1975) and Leech’s mxims of politeness principle. Through analysing the language used by politicians in the talk show Today;s Dialogue, it was found that there were violation and application of politeness in their effort to realize their ideology, which is power.
Keywords: Dialogue, politeness, and power